ELIT AGAMA DAN HARMONISASI SOSIAL DI PALANGKA RAYA - HM, Abubakar; Mualimin, Mualimin; Nurliana, Nurliana (UIN Antasari, 2018)
Abstract: This paper aims to analyze the social interaction among the religious elites in Palangka Raya. The focus of this writing was the patterns of interaction among the religious elites, the encouraging factors of interaction, and the implications of interaction among the religious communities towards the social life among the religious communities in Palangka Raya. This research is a field research using a qualitative method. The data was collected through observation and interview. It was concluded that the interaction among the religious elites in Palangka Raya was supported by the integrative strengths which enable the harmonious relationship among the religious elites. These integrative strengths were the cultural values which have rooted and have been inherited to the next generations, especially to Dayak society. The religious difference in Dayak culture is not seen as the opposing form, but as a human right and a personal choice of each person. On this level the patterns of interaction which will be formed is integrative solidarity. The harmonious relationship among the religious elites then has implications towards the social life among the religious communities. These implicationswere the realization of the harmonious and collaborative relationships among the religious communities in Palangka Raya. Paper ini bertujuan untuk menganalisis interaksi sosial antara elit agama di Palangka Raya. Fokus kajian dalam tulisan ini terkait dengan pola interaksi elit agama, faktor pendorong interaksi, dan implikasi interaksi antara elit agama terhadap kehidupan sosial antar umat beragama di Kota Palangka Raya.Penelitian ini merupakan penelitian lapangan dengan menggunakan metode kualitatif.Untuk memperoleh data dilakukan dengan observasi dan wawancara.Hasil temuan dapat disimpulkan bahwa interaksi antarelit agama di Kota Palangka Raya ditopang oleh kekuatan integratif yang memungkinkan terjadinya hubungan harmonis antara elit agama.Kekuatan integratif tersebut adalah nilai-nilai budaya yang telah mengakar dan diwariskan secara turun-temurun khususnya pada masyarakat Dayak. Perbedaan agama dalam budaya Dayak tidak dipandang sebagai bentuk pertentangan, tetapi sebagai hak asasi dan pilihan pribadi setiap orang. Pada tataran ini pola interaksi yang akan terbentuk adalah bersifat solidaritas integratif. Hubungan yang harmonis antara elit agama kemudian berimplikasi pada kehidupan sosial antarumat beragama di Palangka Raya. Implikasi tersebut terutawa terwujudnya hubungan yang harmonis dan kolaboratif antarumat beragama di Palangka Raya.